PERBANDINGAN KOMPOSISI NUTRISI SUSU KERBAU (Bubalus bubalis) DARI TIGA WILAYAH BERBEDA DI PULAU SUMBAWA - Wandira, Ica Ayu; Dohi, Muhammad; Manaki, Gempar (JANHUS: Jurnal Ilmu Peternakan Journal of Animal Husbandry Science, 2025)
Buffalo milk (Bubalus bubalis) is known for its high nutritional content and has significant potential as a raw material for economically valuable dairy products. This study aims to analyze and compare the nutritional composition of buffalo milk including water content, dry matter, crude protein, crude fat, and minerals from three regions on Sumbawa Island (the districts of Sumbawa, Dompu, and Bima), as well as to identify the factors that influence these variations. The research employed a descriptive-comparative design involving 15 lactating female buffaloes that were traditionally managed (five animals from each district). Milk samples were collected directly from farmers, stored under controlled conditions, and analyzed in the laboratory using proximate analysis. The results show clear regional differences in nutritional composition. Buffalo milk from Dompu exhibited the highest nutritional quality, while Sumbawa had the lowest values, with Bima falling in the intermediate range. In contrast, mineral content was similar across all regions and tended to be lower than values reported in previous studies. These variations were associated with differences in feed quality, soil fertility (including the influence of volcanic soils), the supplementation of leguminous feed, physiological condition and lactation stage, as well as possible genetic variation. Overall, environmental factors and genetic characteristics play an important role in determining the nutritional quality of buffalo milk on Sumbawa Island.